The power of the other : the startling effect other people have on you, from the boardroom to the bedroom and beyond-- and what to do about it - Cloud, Henry (Harper Business, an imprint of HarperCollinsPublishers, 2016)
Most leadership coaching focuses on helping leaders build their skills and knowledge and close performance gaps. These are necessary, but not sufficient. Using evidence from neuroscience and his work with leaders, Dr. Henry Cloud shows that the best performers draw on another vital resource: personal and professional relationships that fuel growth and help them surpass current limits. Popular wisdom suggests that we should not allow others to have power over us, but the reality is that they do, for better or for worse. Consider the boss who diminishes you through cutting remarks versus one who challenges you to get better. Or the colleague who always seeks the limelight versus the one who gives you the confidence to finish a difficult project. Or the spouse who is honest and supportive versus the one who resents your success. No matter how talented, intelligent, or experienced, the greatest leaders share one commonality: the power of the others in their lives. Combining engaging case studies, persuasive findings from cutting-edge brain research, and examples from his consulting practice, Dr. Cloud argues that whether you're a Navy SEAL or a corporate executive, outstanding performance depends on having the right kind of connections to fuel personal growth and minimize toxic associations and their effects. Presenting a dynamic model of the impact these different kinds of connections produce, Dr. Cloud shows readers how to get more from themselves by drawing on the strength and expertise of others. You don't have a choice whether or not others have power in your life, but you can choose what kinds of relationships you want.